Synthesis and biological evaluation of novel benzo[c][1, 2, 5]thiadiazol-5-yl and thieno[3, 2-c]- pyridin-2-yl imidazole derivatives as ALK5 inhibitors. Issue 16 (15th August 2019) - Guo, Zhen; Song, Xiaowei; Zhao, Li-Min; Piao, Ming Guan; Quan, Jishan; Piao, Hu-Ri; Jin, Cheng Hua
Graphical abstract: Effect of compound 14c on TGF-β1-induced Smad2 phosphorylation. Highlights: Two series of imidazole derivatives were designed and synthesized. Compound 14c showed 16.1-fold and 1.8-fold activity of clinical candidates LY-2157299 and EW-7197, respectively. Anticancer activity evaluation of 14c was performed against SPC-A1, HepG2 and HUVEC cells. Abstract: Transforming growth factor (TGF-β), a key mediator of tumor growth and metastasis, has been recognized as an important cancer drug target. A series of benzo[ c ][1, 2, 5]thiadiazol-5-yl imidazoles (14a –g ) and thieno[3, 2- c ]-pyridin-2-yl imidazoles (20a –g ) were designed, synthesized, and evaluated for their activin receptor-like kinase 5 (ALK5) activities. Among these compounds, 14c showed the highest activity (IC50 = 0.008 μM) against ALK5 kinase, which was 16.1-fold and 1.8-fold higher than those of positive control compounds LY -2157299 (IC50 = 0.129 μM) and EW-7197 (IC50 = 0.014 μM), respectively. Compound 14g (350) showed the highest selectivity index of ALK5 against p38α MAP kinase, which was significantly higher than that of positive control compounds LY -2157299 (4) and EW -7197 (211). The inhibitory effects of compound 14c on TGF-β-induced Smad signaling and cell motility were studied in SPC-A1, HepG2 and HUVEC cells using western blot analysis and wound healing assay. ADMET prediction analysis showed that compounds 14c and 14g had good pharmacokinetics and drug-likeness behaviors.